2024
DOI: 10.1002/adma.202310999
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible 2D Materials via Liquid Phase Exfoliation

Yilin He,
Andrés Felipe Andrade,
Cécilia Ménard‐Moyon
et al.

Abstract: Two‐dimensional materials (2DMs), such as graphene, transition metal dichalcogenides (TMDs) and black phosphorus (BP), have been proposed for different types of bioapplications, owing to their unique physicochemical, electrical, optical and mechanical properties. Liquid phase exfoliation (LPE), as a one of the most effective up‐scalable and size‐controllable methods, is becoming the standard process to produce high quantity of various 2DM types as it can benefit of the use of green and biocompatible conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 132 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…The liquid exfoliation method is currently the most commonly used technique for large-scale production of BP nanoparticles ( He et al, 2024 ). Immersion of bulk BP crystals in an organic solvent creates ionic exchange between BP layers, which causes bulk BP to exfoliate and form monolayer BPNSs.…”
Section: General Synthesis Of Bp Nanoparticlesmentioning
confidence: 99%
“…The liquid exfoliation method is currently the most commonly used technique for large-scale production of BP nanoparticles ( He et al, 2024 ). Immersion of bulk BP crystals in an organic solvent creates ionic exchange between BP layers, which causes bulk BP to exfoliate and form monolayer BPNSs.…”
Section: General Synthesis Of Bp Nanoparticlesmentioning
confidence: 99%
“…This comprehensive elucidation of the sequential steps involved in the peptide-mediated exfoliation and functionalization of graphene nanosheets enhances the existing knowledge in the field, providing valuable insights for the design and synthesis of peptide-based materials with tailored properties for various applications, especially in the biomedical field. 11 In conclusion, this study delved into the role of amphiphilic peptides with aromatic amino acids in the exfoliation of graphite and the functionalization of graphene. It was observed that peptides containing tryptophan were more efficient in exfoliating graphite compared with those with phenylalanine or tyrosine.…”
Section: Thementioning
confidence: 99%
“…Drawing on the innovative work that initially proposed the strong noncovalent binding of histidine-rich peptides and others to graphitic surfaces, this mechanistic study of aromatic peptides for the exfoliation and functionalization of graphene-based nanomaterials further advances the understanding of the feasibility of employing amphiphilic peptides in these processes. This comprehensive elucidation of the sequential steps involved in the peptide-mediated exfoliation and functionalization of graphene nanosheets enhances the existing knowledge in the field, providing valuable insights for the design and synthesis of peptide-based materials with tailored properties for various applications, especially in the biomedical field …”
mentioning
confidence: 91%
See 2 more Smart Citations